CHANGES IN CHLOROPHYLL, NITROGEN, PROTEIN, AMINO ACID AND SOME ENZYME CONTENTS IN BETELVINE LEAVES INFECTED WITH XANTHOMONAS CAMPESTRlS PV. BETLlCOLA - NEMA, A. G. (Indian Phytopathology, 2002)
Reduction in total chlorophyll as well as in chlorophyll ’a’ and ’b’ content separately was more pronounced in highly susceptible cultivars. There was no appreciable difference in nitrogen and protein contents of different betelvine cultivars. The quantity of amino acids in resistant cultivar was about 50 per cent more than that in moderately and highly susceptible cultivars and when the leaves were inoculated, amino acids content depleted in all the cultivars. The depletion was faster in highly susceptible cultivar. In healthy leaves, the peroxidase activity of resistant and moderately susceptible cultivars was about 25 per cent more. But, as a result of inoculation, the peroxidase activity as well as polyphenoloxidase activity increased.